Low ERCC1 expression is a good predictive marker in lung adenocarcinoma patients receiving chemotherapy based on platinum in all TNM stages - a single-center study - Marina Piljić Burazer; Suzana Mladinov; Antonela Matana; Sendi Kuret; Joško Bezić; Merica Glavina Durdov (BMC, 2019)
Abstract Background High ERCC1 expression is thought to be related with resistance to chemotherapy based on platinum. The aim of this study was to present our institutional observations regarding to the association of ERCC1 and overall survival (OS) of the lung adenocarcinoma patients who received chemotherapy based on platinum. Material/methods A total of 253 lung adenocarcinoma patients in all TNM stages were retrospectively investigated. The diagnosis was based on small biopsy samples obtained during bronchoscopy. Depending on the TNM stage of the disease and clinical condition, patients received only the chemotherapy based on platinum, or in combination with radiotherapy or surgery. Tissue sample for ERCC1 immunohistochemical analysis was sufficient in 129 patients. Low from high ERCC1 expression was separated by the semi-quantitative H-score median. Results High ERCC1 expression was found in 47.3% patients, and was correlated with higher TNM (p = 0.021), tumor enlargement (p = 0.002), positive lymph nodes (p = 0.001), positive distant metastasis (p = 0.005), and higher relative risk of death (p < 0.001). Furthermore, significance association was observed for low ERCC1 expression and better performance status (ECOG) (p = 0.023). Longer OS was strongly associated with a low ERCC1 expression, not only in the group of patients in TNM stage I-III, who were treated with combination of chemotherapy with surgery or radiotherapy (p = 0.002), but also in the group of patients in TNM stage IV who received only chemotherapy based on platinum (p < 0.001), compared with the patients in the same TNM stage and high ERCC1 expression. Conclusions ERCC1 expression in lung adenocarcinoma is a useful prognostic marker and moreover, a useful predictive marker in patients receiving chemotherapy based on platinum in all stages of the disease.